The Three Faces of Inanna: an Approach to her Polysemic Figure in her descent to the Netherworld - Cabrera, Fernando Rodrigo (2018)
This paper will analyse the polysemous figure and liminal role of the Sumerian goddess of war and love, Inanna, which is traced in diverse mythical compositions. In particular, Inanna´s Descent to the Netherworld will be studied, since in this text from the Old Babylonian period (second millennium BCE) the three aspects that make up the divine personality of the deity can be recognised, i.e. as dea dolens, betrayer, and mater dolorosa. An approach to the story is proposed which considers the roles performed by the other characters and the semantic (or content) and syntactic (or structural) dimensions that organise the narrative.